Star Excursion Balance Test performance varies by sport in healthy Division I collegiate athletes - Stiffler, M. R.; Sanfilippo, J. L.; Brooks, M. A.; Heiderscheit, B. C. (Journal of Orthopaedic & Sports Physical Therapy, 2015)
Study Design Cross-sectional. Objectives To describe performance and asymmetry on the Star Excursion Balance Test (SEBT) by gender and sport, and to determine if differences exist within a collegiate athlete population. Background SEBT performance may differ between genders and levels of competition, though results have been inconsistent. Investigation of performance and asymmetry differences between sports is limited. Gender- and sport-specific reference values likely need to be determined to best assess SEBT performance. Methods SEBT performance was retrospectively reviewed for 393 healthy NCAA Division I collegiate athletes from 8 sports. Means, standard deviations, and 95% confidence intervals were calculated for all variables. Normalized reach distance (% limb length) and asymmetry between limbs were compared for the anterior (ANT), posterolateral (PL), and posteromedial (PM) directions and composite (COMP) score using a 2-way gender x sport ANOVA and a 1-way ANOVA to separately compare sports within each gender. Results Average normalized reach distance ranged from 62% to 69%, 84% to 97%, 99% to 113%, and 82 to 92% in the ANT, PL, and PM directions and COMP score, respectively. Normalized asymmetry ranged from 3 to 4%, 5 to 8%, and 5 to 6% in the ANT, PL, and PM directions. A significant gender x sport interaction (P = .039) was observed in the ANT direction, with a gender effect for soccer players (P < .001, men < women). Significant differences were observed in the PL and PM directions and COMP score among women's teams, with women's ice hockey players reaching the farthest (COMP, 90.0%). Among men's teams, significant differences were observed in all directions and COMP score. Men's ice hockey players (COMP, 91.9%) and wrestlers achieved the farthest distances (COMP, 88.8%). Conclusion SEBT performance varies by team, with a difference between genders also present for soccer. Athletes' performance on the SEBT, and potential injury risk, should be interpreted within the context of their sport.